Salivary SARS-CoV-2 load reduction with mouthwash use: A randomized pilot clinical trial. Issue 6 (June 2021) - Eduardo, Fernanda de Paula; Corrêa, Luciana; Heller, Debora; Daep, Carlo Amorin; Benitez, Carlos; Malheiros, Zilson; Stewart, Bernal; Ryan, Maria; Machado, Clarisse Martins; Hamerschlak, Nelson; Rebello Pinho, João Renato; Bezinelli, Letícia Mello
Abstract: The saliva of patients with COVID-19 has a high SARS-CoV-2 viral load. The risk of spreading the virus is high, and procedures for viral load reduction in the oral cavity are important. Little research to date has been performed on the effect of mouthwashes on the salivary SARS-CoV-2 viral load. This pilot randomized single-center clinical trial investigated whether three types of mouthwash with solutions containing either 0.075% cetylpyridinium chloride plus 0.28% zinc lactate (CPC + Zn), 1.5% hydrogen peroxide (HP), or 0.12% chlorhexidine gluconate (CHX) reduce the SARS-CoV-2 viral load in saliva at different time points. Sixty SARS-CoV-2-positive patients were recruited and randomly partitioned into a placebo (oral rinsing with distilled water) group and other groups according to the type of mouthwash. Saliva samples were collected from the participants before rinsing (T0), immediately after rinsing (T1), 30 min after rinsing (T2), and 60 min after rinsing (T3). The salivary SARS-CoV-2 viral load was measured by qRT-PCR assays. Rinsing with HP and CPC + Zn resulted in better reductions in viral load, with 15.8 ± 0.08- and 20.4 ± 3.7-fold reductions at T1, respectively. Although the CPC + Zn group maintained a 2.6 ± 0.1-fold reduction at T3, this trend was not observed for HP. HP mouthwash resulted in a significant reduction in the SARS-CoV-2 viral load up to 30 min after rinsing (6.5 ± 3.4). The CHX mouthwash significantly reduced the viral load at T1, T2, and T3 (2.1 ± 1.5-, 6.2 ± 3.8-, and 4.2 ± 2.4-fold reductions, respectively). In conclusion, mouthwash with CPC + Zinc and CHX resulted in significant reductions of the SARS-CoV-2 viral load in saliva up to 60 mins after rinsing, while HP mouthwash resulted in a significant reduction up to 30 mins after rinsing. Despite this transitory effect, these results encourage further studies and suggest that these products could be considered as risk-mitigation strategies for patients infected with SARS-CoV-2. Abstract : SARS-CoV-2, Saliva, Antimicrobial agents, Hydrogen peroxide, Chlorhexidine gluconate, Cetylpyridinium